Child disability, welfare payments, marital status and mothers' labor supply: Evidence from Australia - Zeng-Hua Lu; Alec Zuo (Cogent Economics & Finance, 2017)
This paper studies the effects of child disability on mothers' participation in the labor force using Australian data. We formulate a bivariate Probit model in which mothers' employment and welfare recipient status are treated as the dependent variables and child disability is responsible for the both dependent variables. Several propositions concerning the impacts of child disability on Australian mothers' participation in the labor force are tested. Our testing procedure involves one-sided restrictions under the null or alternative hypotheses. Our main findings are as follows. A more severe child disability imposes greater restrictions on single mothers' participation in the labor force. Single mothers are less likely than mothers with a partner to participate in the labor force in the event of a child health shock. There is some evidence of the disincentive effect of welfare payments in encouraging mothers' participation in the labor force, particularly for single mothers.
Keywords: 330; hild disability; extended MaxT test; female labor supply; one-sided test